Pojęcie i zakres ochrony prawnej zabytków archeologicznych w prawie polskim i w prawie międzynarodowym - Artemiuk, Jakub (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article tries to give an insight to the issue of the legal protection of archaeological monuments in Polish and international law. The scope of work includes the description and comparison of the most important legal acts regulating the protection of archaeological sites in Poland and at the international level. Besides Polish law, the UNESCO Convention on the Protection of the Underwater Cultural Heritage and the European Convention on the Protection of the Archaeological Heritage Revised are taken into consideration. The most important issues concerning the legal protection of archaeological heritage are formulation of a correct definition of archaeological heritage and the scope of enactment of the legal acts devoted to the protection of cultural heritage and archaeological sites. This paper presents the controversies concerning the subject, especially taking into account the difficulties in the creation of a synthetic and precise definition of an archaeological monument.
Keywords: prawo międzynarodowe; prawo polskie; ochrona prawna; zabytki archeologiczne